Facile electrodeposition of poly(3,4-ethylenedioxythiophene) on poly(vinyl alcohol) nanofibers as positive electrode for high-performance asymmetric supercapacitor - Dasdevan, Nivekthiren; Mohd Abdah, Muhammad Amirul Aizat; Sulaiman, Yusran (MDPI AG, 2019)
Poly(vinyl alcohol)/poly(3,4-ethylenedioxythiophene) (PVA/PEDOT) nanofibers were synthesized as a positive electrode for high-performance asymmetric supercapacitor (ASC). PVA/PEDOT nanofibers were prepared through electrospinning and electrodeposition meanwhile reduced graphene oxide (rGO) was obtained by electrochemical reduction. The PVA/PEDOT nanofibers demonstrated cauliflower-like morphology showing that PEDOT was uniformly coated on the smooth cross-linking structure of PVA nanofibers. In addition, the ASC showed a remarkable energy output efficiency by delivering specific energy of 21.45 Wh·kg−1 at a specific power of 335.50 W·kg−1 with good cyclability performance (83% capacitance retained) after 5000 CV cycles. The outstanding supercapacitive performance is contributed from the synergistic effects of both PVA/PEDOT//rGO, which gives promising materials for designing high-performance supercapacitor applications.